"Commodification of Body Parts in the Global South: Transnational Inequalities and Development Challenges" by Firouzeh Nahavandi - Dy, Catherine Lourdes (Review of Women's Studies; Vol 28 (2018): Review of Women's Studies Volume XXVIII (2018), 2023)
---